The Educational Inspection, an uncertain future - Avelino SARASÚA ORTEGA (Ediciones Universidad de Salamanca, 2019)
The Educational Inspection has always been a reference for educational centers and for teachers. It has been considered as an important factor for the improvement of the educational system and a key element for the quality of education. However, the incidence and relevance of the inspection is decreasing for both the educational administration and the centers themselves. The Educational Inspection is an institution that at the moment has a serious identity crisis. The article has two distinct parts. In the first one, a brief analysis of the current moment of the Inspection is made, making reference to its origin and its brief history. Topics such as functions, attributions, organic and functional dependency and the requirement and form of access are treated. In the second, some of the challenges you have to face are plated.